Cockers directory - Anima, Nid A. ([S.l.] Y. Anima, 1998)
It contains articles relating to Philippine cockfighting. It also has a list of cockers in the country.
A folio of Filipino sabungeros which includes their lives, hobbies, interests, how they got started and how they manage to live as sabungeros.
Cover title : Cockers directory : a folio of Filipino sabungeros.
Keywords: Cockers (Persons) -- Philippines -- Directories; Cockers (Persons) -- Philippines